Australia's Linkages with China : Prospects and Ramifications of China's Economic Transition - Karam, Philippe (IMF Working Papers; Working Paper ;, 2018)
China and Australia have increasingly strong links, especially through trade. These are driven by demand from China for Australian commodities (coal and iron ore) and services (tourism and education). These links are influenced by China's transition to a services-driven, consumer-led economy. Using ANZIMF, the Australia-New Zealand Integrated Monetary and Fiscal model, three risks (both upside and downside) to China during this transition process are considered, focusing on their spillovers to Australia. One simple takeaway is central to each risk - while the real GDP response to shocks in Australia typically is small, responses in demand components or sectors are usually much larger- along with three further takeaways, all of which help in the analysis of Australia in relation to any risk emanating from China.